Substitution of Soy Protein for Casein Prevents Oxidative Modification and Inflammatory Response Induced in Rats Fed High Fructose Diet. (14th April 2014) - Sreeja, S.; Geetha, Rajagopalan; Priyadarshini, Emayavaramban; Bhavani, Krishnamoorthy; Anuradha, Carani Venkatraman
Abstract : Fructose-rich diet is known to cause metabolic dysregulation, oxidative stress, and inflammation. We aimed to compare the effects of two dietary proteins of animal and plant origins on fructose-induced oxidative stress and inflammatory changes in liver. Wistar rats were fed either starch or fructose (60%) diet with casein or soy protein (20%) as the protein source for 8 weeks. Glucose and insulin, glycated hemoglobin and fructosamine, AOPP, and FRAP were determined in circulation. Intracellular ROS, oxidatively modified proteins (4-HNE and 3-NT adducts), adiponectin, TNF- α, IL-6 and PAI-1 mRNA expression, phosphorylation and activation of JNK and IKK β, and NF- κ B binding activity were assayed in liver. In comparison with starch fed group, fructose + casein group registered significant decline in antioxidant potential and increase in plasma glucose, insulin, and glycated proteins. Increased ROS production, 4-HNE and 3-NT modified proteins, JNK and IKK β activation, and NF- κ B binding activity were observed in them along with increased gene expression of PAI-1, IL-6, and TNF- α and decreased adiponectin expression. Substitution of soy protein for casein reduced oxidative modification and inflammatory changes in fructose-fed rats. These data suggest that soy protein but not casein can avert the adverse effects elicited by chronic consumption of fructose.